Rib‐Type Photonic Wires: A Theoretical Study on Rib‐Type Photonic Wires Based on LiNbO3 Thin Film on Insulator (Adv. Theory Simul. 10/2019). Issue 10 (6th October 2019) - Xu, Qing; Shao, Yan‐Xue; Piao, Rui‐Qi; Chen, Feng; Wang, Xiao; Yang, Xiao‐Fei; Wong, Wing‐Han; Pun, Edwin Yue‐Bun; Zhang, De‐Long
Abstract : In article number1900115, Qing Xu, De‐Long Zhang, and co‐workers simulate a rib‐type LiNbO3 ‐on‐insulator (LNOI) photonic wire (PW). The rib‐type LNOI PW constructs a platform used for developing various ultra‐compact micro‐photonic devices, such as electro‐optic modulator, micro‐ring resonator, grating coupler, as well as various nonlinear devices based on periodically poled LNOI (PPLNOI) PW.